2016
DOI: 10.1016/j.jngse.2016.03.101
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of black- and volatile-oil fluid properties with application to immiscible/miscible gas injection

Abstract: Black-oil fluid properties are determined by lab measurements or can be calculated through flash calculations of the reservoir fluid. Allowing for variable bubble-point pressures in black-or volatile-oil models requires a table of fluid properties be extended above the original bubble-point. Reservoir simulation accuracy, however, may be affected by discontinuities in the input data and poor predictions of extrapolated fluid properties. Common practice is to add surface gas to the original oil in the lab and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It should be noted that in this study and another similar study [10], the MMP was measured by using the vanishing interfacial tension (VIT) method, which has been shown to have significant limitations even for conventional reservoirs [53]. Nojabaei and Johns [54] studied the effect of large gas-oil capillary pressure on fluid properties and saturation pressures when the produced gas was injected to enhance oil recovery. They showed that as the original oil mixed with the injection gas, the effect of capillary pressure on recoveries would get smaller.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in this study and another similar study [10], the MMP was measured by using the vanishing interfacial tension (VIT) method, which has been shown to have significant limitations even for conventional reservoirs [53]. Nojabaei and Johns [54] studied the effect of large gas-oil capillary pressure on fluid properties and saturation pressures when the produced gas was injected to enhance oil recovery. They showed that as the original oil mixed with the injection gas, the effect of capillary pressure on recoveries would get smaller.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Recent studies visualized the gas sweep volume in ultra-tight shale plugs by using CT images [33,58], indicating that gas could make contact with the oil that is trapped in nanosized pores. Furthermore, the nanoconfinement effect may influence the estimations of MMP and alter the fluid properties, so the inclusion of capillary pressure effect and the shift in critical properties results in more accurate recovery prediction [52,54]. In addition, the mechanism of molecular diffusion in shale reservoirs is controversial in the literature.…”
Section: Gas Flooding Performance Evaluationmentioning
confidence: 99%
“…The superiority of gas-injection-based EOR methods is attributed to the increased reservoir energy (pressure) that can enhance production. Their effectiveness can be further augmented through the use of miscible gases, the dissolution of which in the oil enhances its mobility because of a reduction in its viscosity and density, in addition to a reduction in the oil-gas capillary pressure (Nojabaei and Johns 2016;Du et al 2018).…”
Section: Introductionmentioning
confidence: 99%